2008
DOI: 10.1111/j.1468-2982.2008.01662.x
|View full text |Cite
|
Sign up to set email alerts
|

Headache and Multiple Sclerosis: A Population-Based Case-Control Study in Catania, Sicily

Abstract: Ethanol stimulating transient receptor potential vanilloid 1 (TRPV1) on primary sensory neurons promotes neurogenic inflammation, including calcitonin gene-related peptide (CGRP)-mediated coronary dilation. Alcoholic beverages trigger migraine attacks and activation of trigeminal neurons plays a role in migraine. We have investigated in guinea pigs whether ethanol by TRPV1 stimulation causes neurogenic inflammation in the trigeminovascular system. Ethanol-evoked release of neuropeptides from slices of dura mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
43
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 25 publications
6
43
1
2
Order By: Relevance
“…As in the meta-analysis run in the above-mentioned studies the following values were obtained (P= 0.02; 1.14-4.58, OR =2.29). 11,12,14 The present study's results were also quite consistent with the above studies. In the present study, the association between MS and migraine was confirmed (P=0.038; OR=1.87); Also in the disjunctive analysis, a significant association was only found between MS and headache without aura (0.04 = P; 1.94 = OR).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…As in the meta-analysis run in the above-mentioned studies the following values were obtained (P= 0.02; 1.14-4.58, OR =2.29). 11,12,14 The present study's results were also quite consistent with the above studies. In the present study, the association between MS and migraine was confirmed (P=0.038; OR=1.87); Also in the disjunctive analysis, a significant association was only found between MS and headache without aura (0.04 = P; 1.94 = OR).…”
Section: Discussionsupporting
confidence: 82%
“…All studies have confirmed the association between migraine and MS. 2,5,11,13 Some studies such as studies done by Vecca, Katsiari and Nicoletti did not find any significant relationship between MS and migraine with aura. 11,12,14 Conversely, the very researchers found a significant association between MS and the occurrence of migraine without aura. As in the meta-analysis run in the above-mentioned studies the following values were obtained (P= 0.02; 1.14-4.58, OR =2.29).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a growing literature describes the frequency and impact of comorbidity in MS [2,29,30] , research regarding methods of comorbidity measurement in this population is lacking. Our findings indicate moderate or better levels of agreement between self-report and medical records for diabetes, hypertension, hyperlipidemia, thyroid disease, chronic lung disease, osteoporosis, irritable bowel syndrome, migraine, heart disease, depression, and anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%